Strategic Management of Religious Moderation in Indonesian Higher Education: An Integrative Islamic Education Perspective - Kurniawan, Ade Fakih; Juhji, Juhji; Mufrodi, Mufrodi; Sumintak, Sumintak (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This study explores the ideological foundations of religious moderation among Indonesian university students and their role as agents of tolerance and inclusivity, emphasising the importance of educational management in strengthening these values. This study used a descriptive qualitative design and collected data through participant observation, in-depth interviews, and FGDs. The tools were an observation schedule, an Interview guide, and an FGD Guide, developed through expert opinion to ensure content, cultural, and context relevance. Data were analysed using Interpretative Phenomenological Analysis (IPA), which involved transcription and immersion, exploratory note-taking, theme identification, pattern recognition, and interpretative synthesis. The results suggest that religious moderation is grounded in universal humanitarian principles shared by Islam and other world religions. Values are systematically internalized by students and reflected in their attitudes, critical thinking, and daily lives. Religious moderation is realised through inclusivity, tolerance, and social harmony, strengthened by intercultural dialogue and reflective engagement. The study concludes that universities strategically manage and strengthen religious moderation by integrating interfaith literacy and community-based learning into the curriculum and extracurricular activities. Hence, it is suggested that universities adopt a strategic approach to disseminate the values of religious moderation. However, more studies are needed to generalize the comparative study across different learning settings.